Body image in obese children: Effects produced by physical exercise program - E. Romero (E-balonmano.com: Revista de Ciencias del Deporte, 2015)
Body image self-perception in obese children is important since it can encourage behaviors leading to social isolation and cause an increase in food intake. The objective of this study was to determine the changes produced in the level of body image satisfaction and the variation in anthropometric indicators of young children in the State of Sonora, Mexico after participating in a program of 40 sessions of physical exercise with an average caloric expenditure of 267 Kcal per session. 119 children were enrolled in the program; they were between the ages of 8 and 11 with a body mass index (BMI) of 26.59 ± 4.2 (kg/m2). They were evaluated before and after the physical activity intervention by means of a Body Image Satisfaction (BIS) Test. The results with significant changes (p ≤ 0.05) between the pre-test and post-test are in weight and height. There are also significant changes observed in self-image in 15 parts of evaluated body segments, mainly in the abdomen, chest, thighs, buttocks, waist, and hips in all children from the experimental group. The results conclude that physical exercise, in spite of not producing significant changes in BMI, can positively modify body image perception.